A 0.1 G-to-20 G integrated MEMS inertial sensor. (7th July 2015) - Yamane, Daisuke; Konishi, Toshifumi; Matsushima, Takaaki; Toshiyoshi, Hiroshi; Masu, Kazuya; Machida, Katsuyuki
Abstract: This paper presents a novel integrated MEMS inertial sensor with a wide range of acceleration from 0.1 G to 20 G (G = 9.8 m/s 2 ) and with a design suitable for CMOS integration. Owing to the high-density of post-processed gold and the multi-metal layer technology, we have implemented different types of single-axis MEMS capacitive inertial sensors on a single chip of 4 × 4 mm 2 in area to obtain a wide sensing range. The estimated Brownian noise was between 82.4 nG/Hz 1/2 and 1.11 µG/Hz 1/2 . The experimental results show that the MEMS sensor has higher sensing resolution than those of conventional MEMS accelerometers.